2019
DOI: 10.1038/s41598-019-53927-3
|View full text |Cite
|
Sign up to set email alerts
|

Defective Proliferation and Osteogenic Potential with Altered Immunoregulatory phenotype of Native Bone marrow-Multipotential Stromal Cells in Atrophic Fracture Non-Union

Abstract: Bone marrow-Multipotential stromal cells (BM-MSCs) are increasingly used to treat complicated fracture healing e.g., non-union. Though, the quality of these autologous cells is not well characterized. We aimed to evaluate bone healing-related capacities of non-union BM-MSCs. Iliac crest-BM was aspirated from long-bone fracture patients with normal healing (U) or non-united (NU). Uncultured (native) CD271highCD45low cells or passage-zero cultured BM-MSCs were analyzed for gene expression levels, and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 110 publications
(120 reference statements)
0
39
0
Order By: Relevance
“…An in vitro study demonstrated that the fibroblast-like cells isolated from atrophic non-union tissues in humans had lower cell proliferation and osteogenic ability (80). El-Jawhari et al (81) showed that BM-MSCs isolated from the iliac crest in patients with a non-union had low proliferative capacity and osteogenic ability compared with those with successful union. In addition, the passage-zero cultured BM-MSCs treated with a mixture of IFNγ, TNFα, IL1, and IL17 showed lower gene expression of indoleamine 2,3-dioxygenase (IDO), prostaglandin E synthetase 2 (PGES2), and TGFβ1, indicating reduced immunosuppressive potential.…”
Section: Atrophic Non-unionmentioning
confidence: 99%
“…An in vitro study demonstrated that the fibroblast-like cells isolated from atrophic non-union tissues in humans had lower cell proliferation and osteogenic ability (80). El-Jawhari et al (81) showed that BM-MSCs isolated from the iliac crest in patients with a non-union had low proliferative capacity and osteogenic ability compared with those with successful union. In addition, the passage-zero cultured BM-MSCs treated with a mixture of IFNγ, TNFα, IL1, and IL17 showed lower gene expression of indoleamine 2,3-dioxygenase (IDO), prostaglandin E synthetase 2 (PGES2), and TGFβ1, indicating reduced immunosuppressive potential.…”
Section: Atrophic Non-unionmentioning
confidence: 99%
“…Therefore, our data support the future clinical applications of iSTAT3-MSCs. If iSTAT3-MSCs, generated after TKA surgery are stored in a freezer, they can be used to resolve bone disorders, including fractures, non-union fractures, and avascular necrosis (51,(54)(55)(56). Furthermore, since after TKA, patients mainly use the non-operated leg, which can lead to injury in the articular cartilage of the knee joint, iSTAT3-MSCs, with enhanced chondrogenic potential, can be used to treat potential cartilage defects of non-operated knees.…”
Section: Discussionmentioning
confidence: 99%
“…Although this indicted little implication of donor age on MSC immunomodulatory functions, more research would be needed to assess this function in other ON-underlying diseases. This research will be particularly important for therapeutic MSCs as defective immunosuppression has been recently reported with a link to complicated bone healing [ 83 ].…”
Section: Age-related Changes In Mscsmentioning
confidence: 99%
“…Additionally, MSCs from adipose tissue samples of type 2 diabetic patients induced lower suppression of PBMCs proliferation, declined expression of anti-inflammatory TGF-β1 and increased expression of proinflammatory mediators, TNF-α and IL-6 [ 191 ]. These data suggested an impairment of diabetic MSC immunomodulatory effect that can affect early phases of bone healing [ 83 ].…”
Section: Mscs In Diabetesmentioning
confidence: 99%